Short-circuit calculation of power systems with power electronics converters considering asymmetrical faults and converter limits - Jie Song; Marc Cheah-Mane; Eduardo Prieto-Araujo; Oriol Gomis-Bellmunt (International Journal of Electrical Power & Energy Systems)
This paper deals with the challenge of short-circuit calculation for power systems dominated by power electronics converters considering both symmetrical and asymmetrical fault events. A novel methodology has been presented to identify the short-circuit equilibrium point considering the grid support control and limitations of power converters. The studied system has been modeled with an element-based steady-state formulation. In particular, the governing equations implemented on converter control, which involve a specific control mode and various potential current saturation states, are included. Then, an iterative approach has been proposed that could efficiently identify the current saturation states of all converters in the studied system corresponding to different fault conditions. Numerical case studies with voltage source converters (VSCs) show that the proposed methodology can accurately identify the short-circuit equilibrium point with different types and depths of short-circuit fault. The short-circuit calculation results have been validated with dynamic simulations.